Comparison of in Vivo Arteriovenous Fistula Volume Flow Measurements Using a Transonic Transit-Time Ultrasound Flow Device and Doppler Ultrasound. Issue 4 (December 2014) - Schroedter, William B.; Burke, Steven K.; Blair, Andrew; Mendenhall, Vince
Introduction: Doppler ultrasound (US) is extensively validated for classification of vascular disease based on velocity calculations. Although widely used to evaluate dialysis access arteriovenous fistulas (AVF), accurate volume flow measurements have proved more elusive, with significant variability resulting in large thresholds for differentiation of normally functioning from failing fistulae. We sought to compare in vivo measurements of AVF blood flow volume measured by the Transonic transit-time ultrasound flow device with those of Doppler US. Methods: Bilateral femoral AVFs (n = 6) were created in swine (n = 3). Comparative volume flow measurements were made at baseline, 15, 30, 60, and 120 minutes after the creation of AVFs with the Transonic device and with Doppler US using an estimated time averaged velocity and the diameter of the vessel to calculate volume flow using the formula: Q = v A = v (π r 2 ), where Q = volume flow, v = time and spatial averaged mean velocity, A = cross-sectional area, and r = radius of the vessel. Repeat measurements (minimum 3) were performed at each time point. Linear and multiple linear regression analyses were performed. Results: Linear regression analyses showed a weak correlation (R 2 = 0.103, p = 0.002) between Transonic and Doppler volume flow measurements. Doppler consistently showed greater volume flow over all time points than Transonic data. Average Transonic values had less variability over time (R 2 = 0.9505) compared with average Doppler measurements (R 2 = 0.7601). Average flow increased over time, regardless of the flow measurement device, consistent with reported clinical observation of AVF maturation process. Multiple linear regression analysis demonstrated correlation between Doppler and Transonic data (R 2 = 0.197, p = 0.013), and provided a formula to estimate Transonic flow measurement from the Doppler data. [Transonic = 113.742 + (0.334 * Doppler)]. Conclusions: Transonic data demonstrated a stronger relationship between volume flow and time than Doppler data, suggesting transit time ultrasound volume flow measurements may be more accurate. Doppler data tended to overestimate volume flow measurements; however, it may be feasible to use a correction factor for Doppler data that predicts Transonic results.